Azide–Alkyne Cycloaddition (CuAAC) in Alkane Solvents Catalyzed by Fluorinated NHC Copper(I) Complex. Issue 5 (29th November 2018) - Topchiy, Maxim A.; Ageshina, Alexandra A.; Gribanov, Pavel S.; Masoud, Salekh M.; Akmalov, Timur R.; Nefedov, Sergey E.; Osipov, Sergey N.; Nechaev, Mikhail S.; Asachenko, Andrey F.
Abstract : A highly efficient and environmentally benign protocol for copper‐catalyzed alkyne–azide cycloaddition (CuAAC) in industrially important alkane solvents was developed. New copper(I) complexes bearing NHC ligands decorated with bulky hexafluoroisopropylalkoxy group [(CF3 )2 (OR)C‐] were first introduced for the process. The complex with isopentyl group [(CF3 )2 (O i Am)C‐] exhibited the best catalytic activity in the reactions of diversely substituted alkyne and azide substrates in alkane solvents, such as hexane, heptane and cyclohexane. The new CuAAC protocol is easily scalable, synthetically robust, and reproducible; it utilizes low catalyst loadings and enables simple isolation of pure products free from any contaminants including residue of the catalyst and starting materials. Abstract : A highly efficient and environmentally benign protocol for copper‐catalyzed alkyne–azide cycloaddition (CuAAC) in industrially important alkane solvents was developed. New (NHC F )Cu I complex decorated with bulky group [(CF3 )2 (O i Am)C–] exhibited the best catalytic activity in the reactions of diversely substituted alkyne and azide substrates in alkane solvents.